7 Executive Strategies to Stabilize the Nursing Workforce. (April 2022) - Virkstis, Katherine; Boston-Fleischhauer, Carol; Rewers, Lauren; Critchley, Nadia; Whitemarsh, Karl; Paiewonsky, Allyson; Gerstenfeld, Rachel
Abstract : The COVID-19 pandemic exacerbated long-standing challenges in the workforce, resulting in a shortage of nurses that has now reached crisis levels. At the same time, there is a concerning "skills gap" that has been emerging for some time. Leaders have typically relied on legacy recruitment and retention strategies to mitigate these challenges, but these will not be sufficient to address staffing gaps. In this article, the authors discuss how current staffing challenges differ from previous workforce shortages and propose 7 executive strategies for C-suite leaders to prepare for the future nursing workforce.